Faktor-Faktor yang Mempengaruhi Kemiskinan di Provinsi Jambi - Muhammad Amali; Andri Devita (J-MAS (Jurnal Manajemen dan Sains), 2022)
This paper analyzes the factors that influence poverty by using panel data from districts/cities in Jambi Province which are presented from 2010-2020. The results of the study used a fixed effect model approach which resulted in per capita expenditure and population which had a significant influence on the number of poor people in districts/cities in Jambi Province. Meanwhile, the variables of economic growth, human development index and labor force do not have a significant effect on poverty in districts/cities in the Jambi Province. Variable relationships are interrelated between districts/cities. The increase in poverty in Batanghari Regency is due to the relationship with the economic conditions of Jambi City with a strong category of 79.40 percent. The decrease in poverty in Bungo Regency is related to the condition of the Sarolangun Regency area with a large correlation of -67.90 percent with a strong category. The increase in poverty in Kerinci Regency is due to the regional linkage of Jambi City with a large correlation of 89.10 percent, a very strong relationship category. For Sungai Penuh City, the increase in poverty is due to the condition of the Jambi City area with a correlation of 65.40 percent in the strong category. For Merangin Regency, the increase in poverty is due to the relationship with regional conditions in Tebo Regency with a large correlation of 95.80 percent in a very strong category. The increase in poverty in Muaro Jambi Regency is related to regional conditions in Batanghari Regency with a large correlation of 72.60 percent in the strong category. The increase in poverty in Tanjabbar Regency is related to the condition of the Tebo Regency area with a correlation of 96.60 percent, the category is very strong. And for the increase in poverty in Tanjabtim Regency, it is related to the condition of the Tanjabbar Regency area with a large correlation of 84.90 percent, the category is very strong.